HUBUNGAN BENIGN PROSTATE HYPERTROPHY DENGAN DISFUNGSI EREKSI DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Nadya Fitriana; Zuhirman "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Both erectile dysfunction (ED) and benign prostate hypertrophy (BPH) are two related health problems experienced by men aged over forty years. BPH and ED highly affect on men’s quality of life (QOL). It’s necessary to do research about the correlation between BPH and ED by using two kinds of valid scores i.e. International prostate symptoms scores (IPSS) for determining the severity of BPH and International index of erectile function-5 (IIEF-5) which as screening for ED on patients of BPH. Aim of this study was to know the description about BPH patients with ED and their relation by using IPSS and IIEF-5. This is a cross-sectional study which analyze the correlation between severity of BPH and ED by using IPSS and IIEF-5 in Urology Clinic of Arifin Achmad Regional General Hospital. Results obtained from 60 subjects who fulfill the inclusion criterias. Highest incidence of BPH patients present on the age group 60-69 years (38.3%). There are 90% patients of BPH with ED. The degree of BPH and ED experienced by patients are mostly severe, respectively 53.3% and 40%. Level of QOL scores is mostly unsatisfied (58.3%). From Spearman test acquired that there is a significant and very strong correlation between the severity of BPH and ED (r=0.836, p<0.001). High incidence for ED on patients of BPH was found and there’s a correlations between severity of BPH and ED where if the severity of BPH is increasing, the severity of ED will be increased too. Key words : BPH, ED, QOL, Age